Influência do polimorfismo no gene da cyp1a2 sobre os efeitos da suplementação com o óleo essencial de hortelã-pimenta (Mentha piperita L.) no desempenho físico de corredores recreacionais - Miranda Neto, Manoel (2023)
Several foods have been proposed to improve physical performance. Peppermint essential oil (PEO) is among these foods, but there is still no data in the literature on its use in athletes and long-term events, and the mechanisms involved are still not clear. Meanwhile, individual variability in the ergogenic response to time to exhaustion (TTE) has been observed, and a possible explanation may be the presence of genetic polymorphisms. The objective of this study was to investigate the influence of PEO supplementation on the TTE of runners and whether the polymorphism in the CYP1A2 gene influences the responses to this supplementation. Forty male recreational runners (36.5±2.0 years; 24.3±0.6 kg/m2; 52.4±1.2 ml.kg.min) performed two procedures in a cross over model, one of which was experimental (500ml of water added with 0.05ml of PEO) and another isovolumetric placebo added with 0.05ml of mint essence. Thirty minutes later, they ran until exhaustion on a treadmill at 70% of VO2max, maintaining the intake of 100 ml of the experimental drink or placebo every 10 minutes during the first 40 minutes of the run. Before and every 10 minutes during exercise, body temperature and heart rate were recorded. Measurements of thermal sensation, thermal comfort and subjective perception of exertion were taken every 10 minutes during the physical test. Urine collection was done before and after exercise to record urinary volume and density. The sweating rate was calculated. Blood samples were taken at rest, immediately after the end of exercise and 2 hours after exercise, to measure Malondialdehyde and Total Oxidizing Capacity. The oral mucosa was collected for genotyping of the CYP1A2 gene. The first 14 runners ran 109.9 ± 7.4 minutes after ingesting the PEO and 98.5 ± 6.7 minutes in the placebo procedure, which was equivalent to a significant improvement of 11.6 ± 5.5% (p =0.009) (original article 1). For the total sample of 40 runners (original article 2), athletes ran 104.0 ± 5.1 minutes after ingesting PEO and 95.5 ± 3.9 minutes in the placebo procedure, which was equivalent to a significant improvement of 9.6 ± 3.6% (p=0.011). After genotypic division, no statistical difference was observed when comparing the experimental and placebo procedures for athletes with the AA genotype (95.6 ± 6.6 minutes; 88.6 ± 4.3 minutes, respectively; p=0.374). For the AC+CC genotype, TTE was significantly higher after ingestion of PEO compared to placebo (113.2 ± 7.4 minutes; 103.1 ± 6.4 minutes, respectively; p=0.026). Athletes with AC+CC genotypes showed a higher percentage of increase in TTE when compared to the AA genotype (14.9 ± 2.9% vs 2.3 ± 4.3% respectively) (p=0.008). No significant changes were observed in thermoregulatory, hydration and blood variables (p>0.05), even after division by genotype (p>0.05). We conclude that PEO increases the TTE of runners, but only in athletes who have the presence of the C allele for the CYP1A2 gene.